Genetic and environmental influences on the germination of basidiospores in the Cryptococcus neoformans species complex - Forsythe, Adrian (My University, 2016)
In basidiomycetous fungi, the viability of gametes is an important component of sexual fitness and can have implications for speciation events. Prior estimates of basidiospore germination are highly variable and the occurrence of reproduction between these lineages suggests that reproductive isolation is incomplete. Genetic incompatibilities during meiosis have been attributed to much of the offspring inviability. However, the influence of environmental factors on basidiospore germination in Cryptococcus are not well known. In this study, we used human opportunistic yeast pathogens, Cryptococcus neoformans and Cryptococcus deneoformans, as models to investigate the potential effects of selected genetic and environmental factors on basidiospore germination. We evaluated basidiospore germination of six genetic crosses by pairing a total of five strains, three intraspecific crosses and three interspecific crosses, between C. neoformans and C. deneoformans. The offspring of genetic crosses were incubated under multiple media and temperature treatments and scored for their germination ability. In general, spores from intraspecific crosses had greater germination potential than those from interspecific crosses. Growth under high temperatures was the most significant influence on basidiospore germination on these crosses. Furthermore, there were notable interaction effects between environmental factors and parental strains or strain pairs on basidiospore germination. The interaction between the sex-specific genes and environmental pressures impact reproductive barriers and blur species distinctions within the Cryptococcus neoformans species complex. And so, reduced viability of hybrid offspring can have implications for Cryptococcus speciation, ecology, and pathogenesis as hybridization events are an effective method of increasing pathogenicity, expanding species distributions and increasing tolerance to novel environments or hosts.
Keywords: Inter-specific cross; intra-specific cross; temperature; medium; genome structure; post-zygotic reproductive isolation; pathogenesis